Gallium isotope fractionation during precipitation of α-GaOOH from aqueous solution - Yuan, Wei; Wang, Zhengrong; Saldi, Giuseppe D.; Cai, Hongming; Zheng, Wang; Schott, Jacques; Chen, Jiubin (Chemical geology, 2024)
Gallium (Ga) has two naturally-occurring stable isotopes: 69Ga (60.1%) and 71Ga (39.9%). Their isotopic ratios were employed as a potential proxy to trace the geochemical behavior of Ga and its analogue Al. Ga is also an important component of many semiconductors. When exposed to aqueous solutions, it may be dissolved and then precipitate as Ga-bearing crystals (e.g., GaOOH). Thus, the exploration of Ga isotope fractionation during α-GaOOH precipitation could be helpful for understanding geochemical behaviors of Ga and other metals (including Al and Fe) during oxyhydroxide precipitation. In this study, three series of precipitation experiments with variable initial aqueous Ga concentrations (about 9.2, 2.0, and 1.8 ppm) were carried out to determine Ga isotope fractionation factor during α-GaOOH precipitation at ∼20 °C and neutral pH as a function of time. The experimental results could be modeled using a Rayleigh precipitation process, in which fractionation factors between crystals and solution (Δ71Gasolid-solution) are between −0.28 and − 0.37‰, depending on the initial Ga concentration and type of matrix anion (Cl− vs. NO3−). This isotope fractionation is significantly smaller in magnitude than the values reported for Ga adsorption on goethite (−0.89‰) and calcite (−1.27‰). The isotope fractionation is mainly caused by the increase in Gasingle bondO bond length from ∼1.84 Å in aqueous GA(OH)4 to ∼1.991 Å in α-GaOOH solid, with a simultaneous change of Ga coordination number from 4 to 6, although kinetic isotope fractionation may play an important role. Our study provides the first experimental evidence of significant Ga isotope fractionation during kinetic oxyhydroxide precipitation, and suggests that the measurable Ga isotope fractionation occurred at water-solid interface and during precipitations can be potentially used for tracing global geochemical cycling of Ga and its analogue Al and Fe.